Examining ICT Interventions for Rural Health System Connectivity: Challenges and Gaps for Improvement: A Systematic Review - Mukalere, Justine; Ssembatya, Richard; Habinka, Annabella (Universitas Bina Darma, 2025)
Community healthcare interventions in Low- and Lower-Middle-Income Countries (LLMICs) frequently face record management issues that hinder effective linkage between community services and national health systems, contributing to persistently high mortality rates. This study aimed to identify and analyze ICT-based community health interventions implemented in LLMICs, evaluate their effectiveness, and explore challenges limiting their impact. A comprehensive literature search was conducted in June 2024 across ACM Library, PubMed, ScienceDirect, and Google Scholar, focusing on studies published between January 2019 and May 2024. Inclusion criteria targeted ICT-based interventions conducted in LLMICs, available in English, with accessible full texts and clearly defined ICT components. Of the 792 records initially screened, only 9 met the eligibility requirements. Most interventions addressed individual components such as data collection, monitoring, consultations, referrals, and reminders. However, they often lacked integrated systems for data management, continuity of care, and follow-up, limiting their long-term effectiveness. While the review was restricted to open-access studies, the findings offer crucial insights into the design and implementation of ICT-based health solutions. The absence of process integration in current interventions remains a major barrier. Future research and policy development should focus on designing comprehensive, integrated ICT frameworks to strengthen community-to-health system linkages and improve health outcomes in LLMICs.